PENGEMBANGAN MEDIA PEMBELAJARAN GAME EDUKASI UNTUK MENINGKATKAN MINAT DAN PEMAHAMAN KONSEP MATERI SUHU DAN KALOR - Masruroh, Awalina Laelatin; Jumini, Sri; Khoiri, Ahmad (AL-QALAM: JURNAL KEPENDIDIKAN, 2024)
The type of research used in this research is Research and Development (RnD). Data collection techniques include: (1) Observation, (2) Questionnaires, (3) documentation. The subjects in this research were students at Ma'arif Mlandi Middle School, class VII B odd semester 2023-2024 academic year. The subject was chosen because the science scores were still low. The results of this research shown: (1) Learning media for educational games in class VII is an interesting media for students. With educational game learning media, students can grasp the material well and the material can be conveyed well so that learning feels more enjoyable. (2) The results of validation by material experts for educational game learning media received a percentage of 93%, including the criteria for being very suitable for use. The validation results by media experts for educational game learning media received a percentage of 87%, which is included in the criteria for being suitable for use. (3) Through learning educational games, students' interest and conceptual understanding of the science material Temperature and Heat is very high, this is based on the post-test scores obtained. The post-test scores obtained by class VII B students obtained the highest score of 100 and the lowest score of 70 with an average of 77.63. The lowest pre-test score obtained was 40 and the highest score was 80 with an average of 56.842. So that students experience increased interest and understanding of the concepts of temperature and heat.